Investigating the Critical Success Factors of Claims Management in Construction Contracts - Cinko, Emine Gokce; Demirkesen, Sevilay; Sadikoglu, Emel; Zhang, Chengyi (Asce-Amer Soc Civil Engineers, 2023)
Claims management is an essential process aiming to avoid, mitigate, evaluate, and handle claims that may arise for various reasons. Claims usually bring up a considerable cost burden and can be disruptive, often resulting in myriad issues ranging from delays in project completion to protracted litigation. Claims administration and management can be challenging and time consuming for all parties; however, the parties can benefit from having an effective claims management program. Therefore, it is of utmost importance to manage claims with respect to contractual items. Considering this troublesome process, there is a need to develop effective strategies for construction firms to best manage claims and their potential impacts on the contract. However, a comprehensive and up-to-date list of factors is still in need for many construction companies. To fill this gap, this study proposes a set of critical success factors to best handle the claims, avoid their devastating consequences, and better manage contractual agreements. In this respect, an in-depth literature review was conducted to determine an initial list of variables. The list was refined based on expert opinion to represent the perceptions of industry practitioners. Then a questionnaire was administered to construction professionals having broad experience in construction contract management. The variables were ranked by the respondents of the questionnaire based on the importance and success levels. Factor analysis was conducted in SPSS to categorize the variables. The main factors that arise are human related, organizational, resource related, and project related. This study provides a comprehensive, but not exhaustive, list of variables and their categorization to consider as part of an effective claims management process. The study is expected to guide both policy makers and industry practitioners in terms of reviewing their claims management strategies against potentially devastating claims and revisiting their strategies in construction contract management.
Keywords: Construction contracts; Claims management; Success factors; Construction industry